Parents’ Socialization of Values in Contemporary Chile: How do Social Class and Parents’ Religion Shape How They Raise their Children? - Santander Ramírez, Eduardo (2020)
This study aims to assess the relationship between the variables of social class and religion in parental preferences regarding the socialization of values in contemporary Chile. Employing data from the 5th Metropolitan Survey of Family and Education, logistic models were estimated that show that upper-class families tend to favor more symbolic-relational values such as good manners and respect for others, while lower classes privilege social promotion values such as hard work and saving capacity. Parents who identify as Evangelical Christians, on the other hand, place a firm emphasis on values such as religious belief.